The Impact of Compensation, Work Discipline, and Work Motivation on Employee Performance (Case study on students working in the MSME sector) - Setiawan, Ananda; Nabela, Nazwa; Indah, Penny Kasuma (FKIP Universitas Lampung, 2023)
This study aims to determine how the impact of compensation (C), work discipline (WD), and work motivation (WM) on the employee performance (EP) students who work in the Micro, Small and Medium Enterprises (MSME) sector. This study used a quantitative method with SEM-PLS to determine the results under study. The questionnaire used in this study uses a research questionnaire that has been used in previous studies. The questionnaire was responded to by 121 students who were studying while working in the Micro, Small and Medium Enterprises (MSME) sector in Universitas Lambung Mangkurat. The results showed that work discipline has a positive and significant effect on employee performance. In addition, work motivation also has a positive and significant effect on employee performance. However, compensation has no effect on employee performance. This shows that the current compensation received by students has not been able to influence students to improve performance, because the compensation received has not been in accordance with the workload carried out by students.Keywords: Compensation, Work Discipline, Work Motivation, Employee PerformanceDOI: http://dx.doi.org/10.23960/E3J/v6i1.71-82